2015
DOI: 10.1177/1933719114549853
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin Is an Estrogen Receptor α-Selective Modulator That Interacts With Helix 12

Abstract: At clinically effective concentrations, phenytoin is a strong ERα cell antagonist but a many-fold weaker agonist. Although it interacts with ERβ LBD residues, phenytoin has no effects on ERβ-only expressing cells. Docking studies indicate phenytoin interacts with the ERα LBD at the hinge of helix 12 and could thereby interfere with the entry of other ER ligands or with the mobility of helix 12, either of which actions could explain phenytoin's antagonism of ER-mediated E2 actions. Our results suggest an explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…The activation of ER was suggested to be responsible for the anticonvulsant effects of oestrogen (Frye, Ryan, & Rhodes, 2009). On the other hand, the commonly prescribed antiepileptic drug phenytoin, behaving as a powerful antagonist of oestradiol but producing agonistic actions in the absence of oestradiol, was characterized as an ER -selective ER modulator (SERM) (Fadiel et al, 2015), which explains the varying efficiency of the drug correlated with the changes in ovarian functions (Hines & Murphy, 2011;Juurlink, Mamdani, Kopp, Laupacis, & Redelmeier, 2003). The GPER-1 receptor was shown to mediate the epileptogenic effect of oestrogen by modulating the oxidative or antioxidative status of the brain tissue (Kurt, Bosnak, Inan, Celik, & Uremis, 2016), while pretreatment with a phyto-oestrogen has exhibited anticonvulsant and neuroprotective effects by improving oxidative stress and apoptosis (Amiri et al, 2017;Elsayed et al, 2018).…”
mentioning
confidence: 99%
“…The activation of ER was suggested to be responsible for the anticonvulsant effects of oestrogen (Frye, Ryan, & Rhodes, 2009). On the other hand, the commonly prescribed antiepileptic drug phenytoin, behaving as a powerful antagonist of oestradiol but producing agonistic actions in the absence of oestradiol, was characterized as an ER -selective ER modulator (SERM) (Fadiel et al, 2015), which explains the varying efficiency of the drug correlated with the changes in ovarian functions (Hines & Murphy, 2011;Juurlink, Mamdani, Kopp, Laupacis, & Redelmeier, 2003). The GPER-1 receptor was shown to mediate the epileptogenic effect of oestrogen by modulating the oxidative or antioxidative status of the brain tissue (Kurt, Bosnak, Inan, Celik, & Uremis, 2016), while pretreatment with a phyto-oestrogen has exhibited anticonvulsant and neuroprotective effects by improving oxidative stress and apoptosis (Amiri et al, 2017;Elsayed et al, 2018).…”
mentioning
confidence: 99%
“…Fadiel et al 63 found that PHEN is a strong estrogen receptor α antagonist at clinically achievable concentrations and at the same time is a weak agonist.…”
Section: Resultsmentioning
confidence: 99%
“…The instructors introduced the class to recent studies reporting on drugs such as dobutamine and phenytoin that are used to treat heart failure and epilepsy respectively, which may interfere with a patient's response to drugs such as tamoxifen. 10,11 Similar events may also occur when patients are coadministered tamoxifen and nutritional supplements containing phytoestrogens such as liquiritigenin. 12 The instructors explained that this type of competition of drugs for binding to the estrogen receptor may lead to drug-drug interactions.…”
Section: Methodsmentioning
confidence: 99%